Rationale design and synthesis of some novel imidazole linked thiazolidinone hybrid molecules as DNA minor groove binders - War, Javeed Ahmad; Srivastava, Santosh Kumar (European Journal of Chemistry, 2020)
A new series of imidazole linked thiazolidinone hybrid molecules was designed and subsequently synthesized through a feasible, three step reaction protocol. The structures of these molecules were established using FT-IR, 1H NMR, 13C NMR and HRMS techniques. In vitro susceptibility tests against some Gram positive (Staphylococcus aureus and Bacillus subtilis) and Gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa) exhibited broad spectrum potency of the molecules. The most potent molecule (S2A7) amongst the screened molecules, showed minimum inhibitory concentration (MIC) value not less than 2.0 µg/mL which was at par with the reference drug Streptomycin. Structure activity relationships revealed nitro and chloro groups being crucial for bioactivity when present at meta position of arylidene ring in 3-(3-(imidazol-1-yl)propyl)-5-(benzylidene)-2-(phenylimino)thiazolidin-4-one. Deoxyribonucleic acid (DNA)and bovine serum albumin (BSA) binding studies for S2A7 under simulated physiological pH were probed using UV-Visible, fluorescence quenching, gel electrophoresis and molecular docking techniques. These studies established that S2A7 has strong binding affinity towards DNA and binds at the minor groove of DNA with binding constant (Kb) of 0.1287×102 L/mol. Molecular docking simulations of S2A7 with DNA and BSA predicted binding affinity of -9.2 and -7.2 kcal/mol, respectively. Van der Waals forces and hydrogen bonding interactions were predicted as the main forces of interaction. With DNA, S2A7 exhibited specific binding affinity towards adenine-thiamine base pairs. The compound S2A7 forms a stable complex with BSA by binding at subdomain IIIA implying high bio-distribution of the compound.